Analysis of root sealing using methylene blue in different endodontic obturation techniques. Literature review - Machaca Albino, Betty (2022)
One of the biggest drawbacks in endodontic filling is the problem of insufficient root sealing, due to the microleakage of bacteria into the canal. The objective of the research was to carry out a narrative review of the characteristics of the use of methylene blue as an evaluator of microleakage in studies that compared the quality of root sealing with different endodontic filling techniques. The research method used was literature review. Methylene blue was used in experimental in vitro studies, which compared filling techniques such as lateral condensation, cold injectable guttapercha, thermomechanics, among others, the sealed dental pieces were immersed in a 1% methylene blue dye at 5% concentration. This procedure allowed reevaluating the samples in different periods of time. In conclusion, for endodontic filling penetration testing, methylene blue is an easy-to-use and reliable option.